Exploring the Wisdom of Prophet Sulaiman’s Story and the Hoopoe Through the Lens of Wahbah Zuhayli in al-Tafsir al-Munir - Simangunsong, Ali Abdurahman; Misnawati, Misnawati (TAFSE: Journal of Qur'anic Studies, 2024)
The Qur'an uses stories as a medium to convey moral messages for the creation of a virtuous human community. Scholars, such as Wahbah Zuhaylī, interpret these stories and derive various lessons and wisdom from them. In his exegesis al-Munīr, Zuhaylī discusses the "fiqh al-hayah" or lessons that can be learned from the interpreted verses. As a result, this article explores the deeper wisdom within the story of Prophet Sulaiman and the hoopoe bird, regarding Zuhaili's al-Munīr exegesis. This research utilizes a library research approach and a descriptive-analytical method. The findings indicate that the story of Prophet Sulaiman and the hoopoe bird offers wisdom on leadership values, interpersonal relationships, wisdom, honesty, and humility in acknowledging the knowledge provided by Allah.